The ENTREPRENEURS' OVERCONFIDENCE IMPACTS COVID-19 BUSINESS GROWTH, CONSIDERING GENDER PERSPECTIVES: ENTREPRENEURS' OVERCONFIDENCE IMPACTS COVID-19 BUSINESS GROWTH, CONSIDERING GENDER PERSPECTIVES - Ni Made, Suci; Ni Luh , Sayang Telagawathi; Made , Amanda Dewanti (Jurnal Mebis, 2023)
This explanatory research aims to examine the effect of entrepreneur overconfidence on business growth during the Covid 19 period from a gender perspective. The study was conducted on 180 SME entrepreneurs who were determined by purposive sampling technique. The data collection method is a survey with a questionnaire instrument, then the data is analyzed by Structural Equation Modeling (SEM). The results of the study show that (1) entrepreneur overconfidence has a positive and significant effect on business growth in SMEs, (2) female entrepreneurs' overconfidence is significantly different from male entrepreneurs. The overconfidence of female entrepreneurs was higher than that of male entrepreneurs during the Covid 19 period, therefore business growth was also higher. It is necessary to develop a program to increase the confidence of entrepreneurs to increase business growth through training and the application of rules that ensure a conducive business climate.